The Performance of the Job Loss Security Scheme in Indonesia: A Systematic Literature Review and Bibliometric Analysis - Putri, Indah Anggoro; Hamzah, Muhammad Zilal; Sofilda, Eleonora (Jurnal Ketenagakerjaan, 2025)
Unemployment protection has become a key element of social policy reform in developing economies, especially amid labor market volatility and global crises. This study conducts a bibliometric and systematic literature review (SLR) of 141 peer-reviewed articles on unemployment insurance and job loss protection from Scopus and Web of Science. Through performance analysis, co-occurrence mapping, and thematic synthesis, it identifies trends in publication growth, key journals, institutional contributors, and conceptual clusters. Research is largely concentrated in high-income countries and driven by multilateral organizations. Key themes include policy instruments, labor market integration, and geographic gaps. Indonesia’s Job Loss Security (JKP) is assessed against global trends, highlighting innovation and implementation challenges. Citation patterns reveal the value of collaboration and open-access publishing. The study informs both research and policy by offering insights into current developments and recommending strategies to improve design, coverage, and institutional coordination for more inclusive unemployment protection in the Global South.